2001
DOI: 10.1109/36.917895
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution target identification from remotely sensed images using a Hopfield neural network

Abstract: Abstract-Fuzzy classification techniques have been developed recently to estimate the class composition of image pixels, but their output provides no indication of how these classes are distributed spatially within the instantaneous field of view represented by the pixel. As such, while the accuracy of land cover target identification has been improved using fuzzy classification, it remains for robust techniques that provide better spatial representation of land cover to be developed. Such techniques could pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
192
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 280 publications
(200 citation statements)
references
References 21 publications
(24 reference statements)
1
192
0
Order By: Relevance
“…This allows performance comparison with the class proportion-defined initialisation and does not introduce any possible unnecessary bias into the result, which may occur using (i) should estimated class proportions be inaccurate. Tatem et al (2001) demonstrated no significant differences in results from the two initialisation techniques.…”
Section: Network Initialisationmentioning
confidence: 94%
See 4 more Smart Citations
“…This allows performance comparison with the class proportion-defined initialisation and does not introduce any possible unnecessary bias into the result, which may occur using (i) should estimated class proportions be inaccurate. Tatem et al (2001) demonstrated no significant differences in results from the two initialisation techniques.…”
Section: Network Initialisationmentioning
confidence: 94%
“…As the pattern prediction technique represents an extension of the method described in Tatem et al (2001), results of both techniques were compared to highlight the need for a dual approach. To determine the success of each technique at recreating the spatial pattern exhibited in the target images, plots of lag against semivariance (a variogram; Curran & Atkinson, 1998), calculated using Eq.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations